Exploring College Choice Experiences of Rural Students Through Creative Nonfiction - Jenna L Gannon (Educational Considerations, 2022)
Rural students pursue post-secondary education at a lower rate than their urban and suburban counterparts. While the college choice process is complex for all students, it is important to further examine this process for rural students because they are an underserved population. This study utilized Perna’s (2006) college choice model to examine the unique experiences of rural students in Kansas through narrative inquiry. This research sought to answer how rural students described their college choice process as well as the lived experiences that they believed affected their choice in college majors. This research found that the college choice process for rural students is incredibly complex and interrelated. This report utilizes creative nonfiction to showcase that while there are many important factors in the rural student college choice process, previous experiences as well as high school supports/people were two of the most influential factors for the participants.
Keywords: rural education; college choice; narrative inquiry; cultural capital; rural habitus